Clouding over the Arabian Sea and the synoptic situation over India during monsoon - MUKHERJEE, A. K.; GURUNADHAM, G.; PADMANABHAM, K. P. (MAUSAM, 1978)
Satellite cloud pictures for the period 1971-75 were analysed to examine the coverage and type of the clouding over the Arabian Sea m relation to two main synoptic features of the monsoon season, namely, (I) Break m monsoon, and (2) Movement of monsoon depressions. It is found that whenever breaks appear and the monsoon trough goes to the foot of the Himalayas, Arabian Sea north of Lat. 15°N is covered with stratocumulus , cloudiness. With the revival of the monsoon, these cloud lines decrease. This situation continues when the monsoon depressions fond and move westwards till they come to Long. 80°E. When the monsoon depressions move further either to the west of Long. 80 E or to the north of Lat. 25 N the stratocumulus cloud lines increase over the Arabian Sea.